Android-Based Educational Game Application at Kasih Ibu Kindergarten: Aplikasi Game Edukasi Berbasis Android Pada Tk Kasih Ibu - Purnomo, Wulan Andang; Putra, Doni; Yandani, Efri (Journal of Vocational Education and Information Technology (JVEIT), 2024)
Educational Game Application Based on Android at TK Kasih Ibu. Educational games are designed to teach users, develop certain concepts and understanding, thereby enhancing user skills and motivating them to engage in learning. TK Kasih Ibu is an Early Childhood Education institution where the teaching process still relies on traditional media such as picture books and chalkboards, with no incorporation of electronic technology, particularly computers, in early childhood learning. Additionally, there is no utilization of educational games as a supportive learning tool. This research aims to develop an Adobe Animate-based educational game application for environmental awareness, enhancing students' self-learning interest through interactive and enjoyable experiences, and providing immediate feedback to deepen their understanding. The educational game application developed in this research uses the waterfall methodology. The outcome of this research will assist TK Kasih Ibu in incorporating computer-based learning media, specifically an educational game titled "Wildlife Park Game," designed to be run on both desktop and Android platforms.